THE CRITICAL DISCOURSE ANALYSIS OF MISTRESS IN THE CASE OF LEGAL WIFE KILLED HER HUSBAND AFFAIRS NEWS - Sugianti Somba (LINGUA : JURNAL ILMIAH, 2022)
Abstract If there is a problem of infidelity, women are always admitted as inmates, and are stigmatized as other ideal women. When women, who get women become mistresses try to provide clarification on the accusations, this shows their resistance. This research has the title "Analysis of the Wife's Discourse Kills Another Ideal Woman in Tiktok Videos" aims to find out how the position of women in a text is. This research is based on the idea, in this video there are two types of women, namely the legal wife and the mistress of her husband. The type of research used is descriptive qualitative. The discourse analysis technique from Teun A van Dijk is used to view video discourse and comments through character elements, macro and micro structures, and focalization. The research results are; that not all women have the same position in a text. This means that not all women are patients, and are always the guilty party, even though they are portrayed as bad person. Key words: Mistress, Wife, Mistress, Tiktok, Discourse Abstrak Jika ada masalah perselingkuhan, perempuan selalu diakui sebagai narapidana, dan distigmatisasi sebagai perempuan idaman lain lainnya. Ketika perempuan yang menjadikan perempuan sebagai selingkuhan mencoba memberikan klarifikasi atas tuduhan tersebut, ini menunjukkan perlawanan mereka. Penelitian ini berjudul “Analisis Wacana Istri Tewaskan Wanita Idaman Lain dalam Video Tiktok” bertujuan untuk mengetahui bagaimana posisi perempuan dalam sebuah teks. Penelitian ini dilatarbelakangi oleh pemikiran, dalam video ini ada dua tipe wanita, yaitu istri sah dan perempuan idaman lain suaminya. Jenis penelitian yang digunakan adalah deskriptif kualitatif. Teknik analisis wacana dari Teun A van Dijk digunakan untuk melihat wacana dan komentar video melalui elemen karakter, struktur makro dan mikro, dan fokalisasi. Hasil penelitian adalah; bahwa tidak semua perempuan memiliki posisi yang sama dalam sebuah teks. Artinya tidak semua wanita adalah pasien, dan selalu menjadi pihak yang bersalah, meskipun mereka digambarkan sebagai orang jahat. Kata kunci: Perempuan idaman lain, Istri, Nyonya, Tiktok, Wacana